The local wisdom-based disaster mitigation literacy of the indigenous Pangandaran community - Damayani, Ninis Agustini; Saepudin, Encang; Rusmana, Agus; Rizal, Edwin; McArthur, James M.B. (Jurnal Studi Komunikasi, 2022)
Disaster mitigation is a series of efforts to reduce disaster risks through physical development, awareness, and capacity building to face disaster threats. Appropriate communication strategies are needed to increase awareness and the ability to cope with disasters. Delivering appropriate, accurate, and reliable messages can build a reliable disaster literacy community. This study aimed to examine disaster mitigation literacy based on the local wisdom of indigenous people in Pangandaran Regency, West Java. The descriptive qualitative method was employed to explain the phenomena and events occuring in the field comprehensively. Data were collected through interviews, observation, and literature study. Meanwhile, the data were analysed systematically through reduction, presentation, and conclusion stages. The key informants were traditional figures in Badud and Pananjung Villages. The results showed that some traditions contain moral, social, and spiritual messages about disaster mitigation. This study concludes that the local wisdom of the Pangandaran community is an appropriate communication strategy to build disaster mitigation literacy.